Reflections on Teaching The Wire: Developing a Radical Pedagogy - Johnson, Lawrence (Radical Teacher, 2018)
This essay applies the concept of the white racial frame (Feagin 2010) in a critical reflection of the authors use of the popular HBO series The Wire. By positioning the authors subjectivity and experiences teaching the series as a pedagogical tool, the author argues that issues of race, gender, and agency are problematic for classroom use. Despite its popularity in academia students are generally ill-prepared to understand a long history of housing policy and residential segregation to their understanding of The Wire. By default, the white spatial imaginary undermines the critical nature of the show because it only depicts the ghetto where the critical task is to explain the structures that created the modern American ghetto.